Hubungan Massage Payudara terhadap Frekuensi Menyusui Ibu Postpartum di Puskesmas Cipondoh Kota Tangerang 2019 - Solihati Solihati; Ika Novita Sari (MOTORIK Jurnal Ilmu Kesehatan, 2019)
Lack of knowledge information about breast massage causes lack of milk production in breastfeeding mothers which can be increased from the frequency of breastfeeding. In Indonesia Nationally, the coverage of infants receiving exclusive breastfeeding is 61.33%. In Banten, the coverage of infants receiving exclusive breastfeeding is 35.87%. The results of the data in 2018 At the Cipondoh Health Center, the coverage of infants getting exclusive breastfeeding was 1,430 with the target of 1,488 infants who were exclusively breastfed. To find out whether there is a relationship between breast massage and the frequency of breastfeeding for postpartum mothers in Cipondoh Public Health Centers. This type of research uses descriptive analytic, cross sectional approach techniques with a population of 32 respondents sampling by accidental sampling. The data analysis technique used was the Chi-Square Test, using SPSS 22. there was a relationship between breast massage and the frequency of breastfeeding for postpartum mothers. p-value 0,000 (p <0.05). from the results of the study there is a relationship between breast massage and the frequency of breastfeeding for postpartum mothers. The impact of breastfeeding mothers can be seen from the frequency of breastfeeding mothers who benefit so that the mother's uterus returns to normal faster.